Research on self presentation and gender differences through facebook profile pictures - Nikolaidou, Myria (Τμήμα Πολυμέσων και Γραφικών Τεχνών, Σχολή Εφαρμοσμένων Τεχνών και Επικοινωνίας, Cyprus University of Technology, 2011)
This dissertation examines self presentation through the means of photography. A gender based analysis is carried out on a sample of 500 profile pictures which belong to both male and female Cypriot residents between 18 and 25 years old. The key objective of this paper concerns the way men and women, in Cyprus see and present themselves online focusing on profile pictures in the context of Facebook. Stereotypes and gender differences do persist among facebook profile pictures as in physical reality of Cypriot community.
Keywords: Social Networks; Κοινωνικά δίκτυα